AR coating solution based on silica sol and preparation method thereof
By using boron crosslinked silicone sol and nano-scale organic emulsion to prepare AR coating solution, the problem of insufficient transmittance and hardness of AR coating in the prior art is solved, the effect of high transmittance and high hardness is achieved, and the boron element is passed Repair and improve the mechanical properties of the coating.
Patent Information
- Application Number
- CN202410284503.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-03-13
AI Technical Summary
The existing AR coating has low light transmittance and hardness, which cannot meet the usage requirements of photovoltaic modules.
Boron crosslinked silicon sol and nano-scale organic emulsion are used as main components to prepare an AR coating solution by emulsion polymerization to form a coating with high crosslinking density and appropriate pore structure, which improves hardness and light transmittance.
A high light transmittance and high hardness AR coating is achieved, which can meet the needs of photovoltaic modules, and repair microcracks through boron elements to improve the mechanical properties of the coating.
Smart Images

Figure CN118240401B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating liquids, and in particular to an AR coating liquid based on silica sol and a preparation method thereof. Background Art
[0002] AR coating, full name anti-reflective film, is a multi-layer composite film system coated on the surface of glass or other optical components through a specific process. Its main purpose is to reduce the reflectivity of light and increase the transmittance of light. This technology is widely used in the manufacture of various optical components such as lenses, filters, reflectors, etc., especially in recent years, with the continuous popularization of the photovoltaic industry, the application of AR coating in photovoltaic modules has gradually expanded, especially the cover glass of photovoltaic modules. At present, AR coating is mainly based on silicate as raw material, which is catalytically reacted to form silica sol, which is then mixed with template agents to form AR coating coating liquid, and finally formed by curing and tempering. However, the silica sol prepared by this method has a low porosity and a high refractive index, so the AR coating formed has a low transmittance and cannot meet the use requirements of photovoltaic modules. In addition, the hardness of the AR coating currently used on the market is not good. Once bumps or scratches occur during the use of photovoltaic modules, it will also affect the transmittance. Therefore, AR coatings with high transmittance and rigidity have gradually become the development trend of the industry.
[0003] The invention patent with application number CN201510312806.9 discloses a chain or network silica sol and a super-hydrophilic self-cleaning anti-reflection coating liquid and its preparation and application. The compound coating liquid is formed by compounding the spherical silica sol and the chain or network silica sol rich in hydroxyl groups, and the composite hybrid silica sol is modified by coupling agents and cross-linking agents. The coating formed by curing the coating liquid has high light transmittance and high hardness, and has industrial application value. Therefore, by designing the formula of the coating liquid, an AR coating with high light transmittance and hardness can be obtained.
[0004] Based on this, the present invention provides an AR coating liquid based on silica sol, and the coating formed after the curing and tempering process has the characteristics of high light transmittance and high hardness, which can meet the relevant needs of photovoltaic modules. Summary of the invention
[0005] The object of the present invention is to provide an AR coating solution based on silica sol and a preparation method thereof, which solves the problems of low light transmittance and low hardness of AR coating.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A silica sol-based AR coating solution comprises the following components in parts by weight:
[0008] 25-35 parts of boron cross-linked silica sol;
[0009] 5-15 parts of nano-scale organic emulsion;
[0010] 0.5-1.5 parts of leveling agent;
[0011] 65-75 parts of organic solvent;
[0012] The nanometer-scale organic emulsion is prepared by emulsion polymerization of coupling monomers and cationic crosslinking agents.
[0013] Furthermore, the boron cross-linked silica sol is prepared by the following method:
[0014] Step 1: Prepare silica sol precursor
[0015] The silane precursor, sodium tetraborate and anhydrous toluene are stirred and mixed, and after being stirred evenly, placed in a temperature condition of 70-75°C, with nitrogen as a protective gas, mechanically stirred for 4-6 hours, and then the nitrogen is withdrawn, the solvent is evaporated and separated, and the material is the silica sol precursor;
[0016] Step 2: Preparation of boron cross-linked silica sol
[0017] Add silica sol precursor and methyl orthosilicate to a mixed solution of isopropanol and purified water, start stirring, and after mechanical stirring at room temperature, add the catalyst. After the addition is completed, start heating and stabilize the temperature at 60-65°C. Maintain this temperature for 3-6 hours, cool and discharge the material to obtain boron-crosslinked silica sol.
[0018] In the above technical scheme, sodium tetraborate is used as a cross-linking agent, which can react with the amino group in the silane precursor structure, thereby realizing cross-linking of the silane precursor and forming a silica sol precursor with boron as the cross-linking center. Under the catalysis of acid, the silica sol precursor and methyl orthosilicate are hydrolyzed and gradually polymerized to form a silica sol containing a boron cross-linking center in the structure, namely, a boron-cross-linked silica sol.
[0019] Furthermore, in step 1, the silane precursor is any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane or N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0020] Furthermore, in step 2, the volume ratio of isopropanol to purified water is 4-5:1.
[0021] Furthermore, in step 2, the catalyst is at least one of hydrochloric acid, phosphoric acid, citric acid or acetic acid.
[0022] Furthermore, the nanoscale organic emulsion is prepared by the following method:
[0023] Step A: Make seed lotion
[0024] Add purified water and emulsifier SE-10N to the reaction kettle. After adding, raise the temperature to 78-80°C and stir evenly. Then add one-fifth of the coupling monomer and cationic crosslinking agent to the kettle. After stirring and dispersing evenly, add three-quarters of the initiator ammonium persulfate to the kettle. After adding, stir for 20-30 minutes to form a seed emulsion.
[0025] Step B: Preparation of Nano-scale Organic Emulsion
[0026] Add the remaining amount of coupling monomer into the kettle, and raise the temperature to 80-82°C, keep it for 10-20 minutes, then add the remaining amount of initiator ammonium persulfate into the kettle, further raise the temperature to 86-88°C, and keep it for 1-2 hours to obtain a nano-scale organic emulsion;
[0027] The nano-scale organic emulsion is prepared by using the following raw materials in parts by weight: 40-50 parts of purified water, 10-12 parts of emulsifier SE-10N, 20-30 parts of coupling monomer, 2-3 parts of cationic crosslinking agent, and 1-2 parts of initiator ammonium persulfate.
[0028] In the above technical scheme, through emulsion polymerization, coupling monomers and cationic crosslinking agents are used as polymerization monomers, and ammonium persulfate is used as an initiator to initiate crosslinking polymerization of the polymerization monomers. The presence of the crosslinking agent can promote the coupling monomer molecules to be more tightly connected together, quickly form emulsion droplets, and limit the growth of droplets, so that the particle size of the prepared emulsion droplets is smaller. At the same time, since the prepared crosslinking agent structure contains quaternary ammonium cationic groups, electrostatic repulsion can exist between the formed emulsion droplets, and then they are evenly dispersed, which is beneficial to improve the stability of the emulsion.
[0029] Furthermore, the coupling monomer is at least one of styrene, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, ethyl methacrylate or glycidyl methacrylate.
[0030] Furthermore, in step A, the cationic crosslinking agent is prepared by the following method:
[0031] Add glycidyl methacrylate, tertiary amine-terminated monomer and cyclohexanone into a reaction kettle, start stirring, and after a homogeneous solution is formed, add the polymerization inhibitor 2,6-di-tert-butyl-p-cresol into the reaction kettle, start heating, and maintain the temperature in the kettle at 60-70°C for 1-2 hours, adjust the pH to 6-7, continue stirring for 2-4 hours, evaporate the solvent, cool and discharge the material to obtain a cationic crosslinking agent.
[0032] In the above technical scheme, the epoxy group in the glycidyl methacrylate structure can undergo a quaternization ring-opening reaction with the tertiary amine group in the tertiary amine-terminated monomer structure to obtain a cationic crosslinking agent having two substituted quaternary ammonium salt functional groups and a polymerizable unsaturated olefin-terminated structure.
[0033] Furthermore, the tertiary amine-terminated monomer is 1,4-bis(dimethylamino)butane or tetramethylhexanediamine.
[0034] Furthermore, the leveling agent is any one of an acrylate leveling agent or a polyether-modified polysiloxane leveling agent; the organic solvent is at least one of methanol, ethanol, isopropanol, propylene glycol, glycerol, dipropylene glycol methyl ether, tripropylene glycol monomethyl ether or tripropylene glycol monoethyl ether.
[0035] A method for preparing an AR coating solution based on silica sol comprises the following steps:
[0036] Step 1. Weigh each raw material according to the weight, mix the boron cross-linked silica sol, the nano-scale organic emulsion and the leveling agent, and stir and mix them evenly at a stirring rate of 300-500 r / min to form a pre-mixed material;
[0037] Step 2: Mix the pre-mixed material with the organic solvent and stir them mechanically to obtain the AR coating solution.
[0038] Beneficial effects of the present invention:
[0039] (A) The present invention adopts boron-crosslinked silica sol as the matrix material of AR coating solution. The silica sol supported by boron crosslinking not only has a higher crosslinking density, but also makes the coating formed after the coating solution is solidified have a very dense three-dimensional grid microstructure and a higher surface density, thereby effectively improving the hardness of the coating. In addition, high temperature will be generated during the tempering process, and high temperature will cause organic matter to volatilize and induce microcracks in the coating. The presence of boron can repair the microcracks generated by high temperature, thereby making the coating show higher mechanical hardness.
[0040] (B) The present invention prepares a nano-scale organic emulsion by adjusting the process and raw materials. Since the emulsion particles are small in size and there is electrostatic repulsion between each other, they can be evenly and orderly arranged in the silica sol, which promotes the formation of orderly arranged pores in the final coating structure, forming a proper pore structure, thereby reducing the refractive index, thereby effectively improving the anti-reflection effect of the coating.
[0041] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0043] Figure 1 It is a scanning electron microscope image of the nano-scale organic emulsion of the present invention. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The boron cross-linked silica sol used in the following examples and comparative examples was prepared by the following method:
[0046] Step 1: Prepare silica sol precursor
[0047] 1.5 g of 3-aminopropyltriethoxysilane, 0.8 g of sodium tetraborate and anhydrous toluene were stirred and mixed, and then placed at 70°C with nitrogen as protective gas. After mechanical stirring for 6 hours, the nitrogen was removed, the solvent was evaporated and the material was separated, which was a silica sol precursor;
[0048] Step 2: Preparation of boron cross-linked silica sol
[0049] Add 15g of silica sol precursor and 5g of methyl orthosilicate to a mixed solution of 100mL of isopropanol and 20mL of purified water, start stirring, and after mechanical stirring at room temperature, add 25mL of 1mol / L phosphoric acid. After the addition, start heating and stabilize the temperature at 60°C. Maintain this temperature for 4h, cool and discharge the material to obtain boron-crosslinked silica sol.
[0050] The nanoscale organic emulsions used in the following examples and comparative examples were prepared by the following method:
[0051] Step A: Cationic crosslinking agent
[0052] 0.6 g of glycidyl methacrylate, 0.4 g of tetramethylhexanediamine and cyclohexanone were added to a reaction kettle, and stirring was started. After a homogeneous solution was formed, 0.01 g of a polymerization inhibitor 2,6-di-tert-butyl-p-cresol was added to the reaction kettle, and heating was started. The temperature in the kettle was maintained at 65° C. for 2 hours, and the pH was adjusted to 7. After stirring for 3 hours, the solvent was evaporated, and the temperature was lowered and discharged to obtain a cationic crosslinking agent;
[0053] Step B: Making seed emulsion
[0054] Add 50g purified water and 10g emulsifier SE-10N to the reaction kettle. After adding, raise the temperature to 80°C and stir evenly. Then add 2.5g styrene, 2.5g methacrylic acid and 2.5g cationic crosslinking agent to the kettle. After stirring and dispersing evenly, add 0.9g initiator ammonium persulfate to the kettle. After adding, stir for 30min to form a seed emulsion.
[0055] Step C: Preparation of nano-scale organic emulsion
[0056] 10g of styrene and 10g of methacrylic acid were added into the kettle, and the temperature was raised to 82°C. After maintaining for 15 minutes, 0.3g of initiator ammonium persulfate was added into the kettle, and the temperature was further raised to 88°C. After heat treatment for 1.5 hours, a nano-scale organic emulsion was obtained.
[0057] The scanning electron microscope image of the nanoscale organic emulsion is shown in FIG. Figure 1 As shown, it can be observed that the nano-scale organic emulsion droplets have an average particle size of about 20 nm, which is relatively small, and the droplets are arranged in an orderly manner, so that the coating can produce appropriate porosity and improve the anti-reflection effect of the coating.
[0058] Example 1
[0059] A silica sol-based AR coating solution comprises the following components in parts by weight:
[0060] 25 parts of boron cross-linked silica sol;
[0061] 5 parts of nano-scale organic emulsion;
[0062] 0.5 parts of polyether modified polysiloxane leveling agent;
[0063] 65 parts of isopropyl alcohol;
[0064] The preparation method of the AR coating solution comprises the following steps:
[0065] Step 1. Weigh each raw material according to the weight, mix the boron cross-linked silica sol, the nano-scale organic emulsion and the polyether modified polysiloxane leveling agent, and stir and mix them evenly at a stirring rate of 300 r / min to form a pre-mixed material;
[0066] Step 2: Mix the pre-mixed material with isopropyl alcohol and stir them mechanically to obtain the AR coating solution.
[0067] Example 2
[0068] A silica sol-based AR coating solution comprises the following components in parts by weight:
[0069] 30 parts of boron cross-linked silica sol;
[0070] Nano-scale organic emulsion 12 parts;
[0071] 1 part of polyether modified polysiloxane leveling agent;
[0072] 70 parts of dipropylene glycol methyl ether;
[0073] The preparation method of the AR coating solution comprises the following steps:
[0074] Step 1. Weigh each raw material according to the weight, mix the boron cross-linked silica sol, the nano-scale organic emulsion and the polyether modified polysiloxane leveling agent, and stir and mix them evenly at a stirring rate of 400 r / min to form a pre-mixed material;
[0075] Step 2: Mix the pre-mixed material with dipropylene glycol methyl ether, and stir them mechanically to obtain the AR coating solution.
[0076] Example 3
[0077] A silica sol-based AR coating solution comprises the following components in parts by weight:
[0078] 35 parts of boron cross-linked silica sol;
[0079] 15 parts of nano-scale organic emulsion;
[0080] 1.5 parts of polyether modified polysiloxane leveling agent;
[0081] 75 parts of tripropylene glycol monoethyl ether;
[0082] The preparation method of the AR coating solution comprises the following steps:
[0083] Step 1. Weigh each raw material according to the weight, mix the boron cross-linked silica sol, the nano-scale organic emulsion and the leveling agent, and stir and mix them evenly at a stirring rate of 500 r / min to form a pre-mixed material;
[0084] Step 2: Mix the pre-mixed material with the organic solvent and stir them mechanically to obtain the AR coating solution.
[0085] Comparative Example 1
[0086] A silica sol-based AR coating solution comprises the following components in parts by weight:
[0087] Silica sol 30 parts;
[0088] Nano-scale organic emulsion 12 parts;
[0089] 1 part of polyether modified polysiloxane leveling agent;
[0090] 70 parts of dipropylene glycol methyl ether;
[0091] The preparation method of the AR coating solution comprises the following steps:
[0092] Step 1. Weigh each raw material according to the weight, mix the silica sol, nano-scale organic emulsion and polyether-modified polysiloxane leveling agent, and stir and mix them evenly at a stirring rate of 400 r / min to form a pre-mixed material;
[0093] Step 2: Mix the pre-mixed material with dipropylene glycol methyl ether, and stir them mechanically to obtain the AR coating solution.
[0094] The preparation method of silica sol is as follows:
[0095] Add 15 g of 3-aminopropyltriethoxysilane and 5 g of methyl orthosilicate to a mixed solution of 100 mL of isopropanol and 20 mL of purified water, start stirring, and mechanically stir evenly at room temperature. Then, add 25 mL of 1 mol / L phosphoric acid. After the addition is completed, start heating and stabilize the temperature at 60°C. Maintain this temperature for 4 hours, cool and discharge the material to obtain boron-crosslinked silica sol.
[0096] Comparative Example 2
[0097] A silica sol-based AR coating solution comprises the following components in parts by weight:
[0098] 30 parts of boron cross-linked silica sol;
[0099] Styrene acrylic emulsion 12 parts;
[0100] 1 part of polyether modified polysiloxane leveling agent;
[0101] 70 parts of dipropylene glycol methyl ether;
[0102] The preparation method of the AR coating solution comprises the following steps:
[0103] Step 1. Weigh each raw material according to the weight ratio, mix the boron cross-linked silica sol, the nano-scale organic emulsion and the polyether modified polysiloxane leveling agent, and stir and mix them evenly at a stirring rate of 400 r / min to form a pre-mixed material;
[0104] Step 2: Mix the pre-mixed material with dipropylene glycol methyl ether, and stir them mechanically to obtain the AR coating solution.
[0105] Wherein the preparation method of styrene acrylic emulsion is:
[0106] Step A: Make seed lotion
[0107] Add 50g purified water and 10g emulsifier SE-10N to the reaction kettle. After adding, raise the temperature to 80°C and stir evenly. Then add 2.5g styrene and 2.5g methacrylic acid to the kettle. After stirring and dispersing evenly, add 0.9g initiator ammonium persulfate to the kettle. After adding, stir for 30 minutes to form a seed emulsion.
[0108] Step B: add 10g styrene and 10g methacrylic acid into the kettle, raise the temperature to 82°C, keep it for 15min, add 0.3g initiator ammonium persulfate into the kettle, further raise the temperature to 88°C, keep it for 1.5h, and obtain nano-scale organic emulsion.
[0109] Test Case
[0110] The photovoltaic glass was cleaned and dried completely, and the coating solution prepared in Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention was evenly coated on the surface of the photovoltaic glass. After being completely cured in a temperature environment of 150°C, the glass was then placed in a temperature environment of 700°C for tempering for 5 minutes, and the following tests were performed:
[0111] , where the transmittance enhancement value is calculated as the transmittance value of the coated photovoltaic glass minus the transmittance value of the original photovoltaic glass.
[0112] The test data in the table are analyzed to show that the AR coating liquid prepared by using the boron cross-linked silica sol prepared by the present invention as the coating base material and using the nano-scale organic emulsion as the template agent has a more excellent anti-reflection effect and a high pencil hardness after being cured to form a coating.
[0113] Comparative Example 1 uses conventional silica sol as the base material, and the crosslinking density of the formed coating is relatively low, and it cannot be repaired by boron, so the hardness is poor. Comparative Example 2 uses styrene acrylic emulsion prepared without adding a crosslinking agent as a template, which makes it difficult to form orderly pores in the coating, so the anti-reflection effect is poor.
[0114] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0115] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. An AR coating solution based on silica sol, characterized in that: The composition comprises the following components in parts by weight: 25-35 parts of boron cross-linked silica sol; 5-15 parts of nano-scale organic emulsion; 0.5-1.5 parts of leveling agent; 65-75 parts of organic solvent; The nano-scale organic emulsion is prepared by emulsion polymerization of coupling monomers and cationic crosslinking agents; The coupling monomer is at least one of styrene, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, ethyl methacrylate or glycidyl methacrylate; The cationic crosslinking agent is prepared by the following method: Add glycidyl methacrylate, tetramethylhexanediamine and cyclohexanone into a reaction kettle, start stirring, and after a homogeneous solution is formed, add the polymerization inhibitor 2,6-di-tert-butyl-p-cresol into the reaction kettle, start heating, and maintain the temperature in the kettle at 60-70°C for 1-2 hours, adjust the pH to 6-7, continue stirring for 2-4 hours, evaporate the solvent, cool and discharge the material to obtain a cationic crosslinking agent.
2. The AR coating solution based on silica sol according to claim 1, characterized in that: The boron cross-linked silica sol is prepared by the following method: Step 1: Prepare silica sol precursor The silane precursor, sodium tetraborate and anhydrous toluene are stirred and mixed, and after being stirred evenly, placed in a temperature condition of 70-75°C, with nitrogen as a protective gas, mechanically stirred for 4-6 hours, and then the nitrogen is withdrawn, the solvent is evaporated and separated, and the material is the silica sol precursor; Step 2: Preparation of boron cross-linked silica sol Add silica sol precursor and methyl orthosilicate to a mixed solution of isopropanol and purified water, start stirring, and after mechanical stirring at room temperature, add the catalyst. After the addition is completed, start heating and stabilize the temperature at 60-65°C. Maintain this temperature for 3-6 hours, cool and discharge the material to obtain boron-crosslinked silica sol.
3. The AR coating solution based on silica sol according to claim 2, characterized in that: In step 1, the silane precursor is any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane or N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
4. The AR coating solution based on silica sol according to claim 2, characterized in that: In step 2, the volume ratio of isopropanol to purified water is 4-5:
1.
5. The AR coating solution based on silica sol according to claim 2, characterized in that: In step 2, the catalyst is at least one of hydrochloric acid, phosphoric acid, citric acid or acetic acid.
6. The AR coating solution based on silica sol according to claim 1, characterized in that: The nano-scale organic emulsion is prepared by the following method: Step A: Make seed lotion Add purified water and emulsifier SE-10N to the reaction kettle. After adding, raise the temperature to 78-80°C and stir evenly. Then add one-fifth of the coupling monomer and cationic crosslinking agent to the kettle. After stirring and dispersing evenly, add three-quarters of the initiator ammonium persulfate to the kettle. After adding, stir for 20-30 minutes to form a seed emulsion. Step B: Preparation of Nano-scale Organic Emulsion Add the remaining amount of coupling monomer into the kettle, and raise the temperature to 80-82°C, keep it for 10-20 minutes, then add the remaining amount of initiator ammonium persulfate into the kettle, further raise the temperature to 86-88°C, and keep it for 1-2 hours to obtain a nano-scale organic emulsion; The nano-scale organic emulsion is prepared by using the following raw materials in parts by weight: 40-50 parts of purified water, 10-12 parts of emulsifier SE-10N, 20-30 parts of coupling monomer, 2-3 parts of cationic crosslinking agent, and 1-2 parts of initiator ammonium persulfate.
7. The AR coating solution based on silica sol according to claim 1, characterized in that: The leveling agent is any one of an acrylate leveling agent or a polyether-modified polysiloxane leveling agent; the organic solvent is at least one of methanol, ethanol, isopropanol, propylene glycol, glycerol, dipropylene glycol methyl ether, tripropylene glycol monomethyl ether or tripropylene glycol monoethyl ether.
8. A method for preparing the AR coating solution based on silica sol as claimed in claim 1, characterized in that: The following steps are involved: Step 1, weigh each raw material according to the weight, and mix the boron cross-linked silica sol, nano-scale organic emulsion and leveling agent, and stir and mix them evenly at a stirring rate of 300-500r / min to form a pre-mixed material; Step 2: Mix the pre-mixed material with the organic solvent and stir them mechanically to obtain the AR coating solution.
